2017
DOI: 10.31234/osf.io/s98ab
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying sources of variability in infancy research using the infant-directed speech preference

Abstract: The field of psychology has become increasingly concerned with issues related to methodology and replicability. Infancy researchers face specific challenges related to replicability: high-powered studies are difficult to conduct, testing conditions vary across labs, and different labs have access to different infant populations, amongst other factors. Addressing these concerns, we report on a large-scale, multi-site study aimed at 1) assessing the overall replicability of a single theoretically-important pheno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…All the data from this study are readily available for reanalysis by other researchers and for use in developing automatic labeling methods and we encourage such data re-use. This work also provides an example for how shared datasets with interoperable classification schema can provide more robust analyses than any single laboratories data alone; this is an important step forward in addressing replicability and reproducibility in psychology (ManyBabies Collaborative, 2017).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…All the data from this study are readily available for reanalysis by other researchers and for use in developing automatic labeling methods and we encourage such data re-use. This work also provides an example for how shared datasets with interoperable classification schema can provide more robust analyses than any single laboratories data alone; this is an important step forward in addressing replicability and reproducibility in psychology (ManyBabies Collaborative, 2017).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…In pursuing this topic, many researchers have fixed their sights on the speech addressed to children. In several languages, child-directed speech (CDS; speech designed for and directed toward a child recipient) has been demonstrated to be distinct from adult-directed speech (ADS) in that it is linguistically adapted for young listeners (e.g., Soderstrom, 2007), interactionally rich (Bruner, 1983), preferred by infants (ManyBabies Collaborative, 2017), and facilitates early word learning (Cartmill et al, 2013;Hoff, 2003;Rowe, 2008;Weisleder & Fernald, 2013).…”
mentioning
confidence: 99%
“…The first (11), examined data across 34 experiments and reported a robust effect size (Cohen's d = 0.72) for a preference of infant-over adult-directed speech by infants. The second, published by the ManyBabiesConsortium (12), involved studies from 67 laboratories across North America, Europe, and Asia, and reported a significant effect size across all studies (Cohen's d = 0.35).…”
mentioning
confidence: 99%